Recognition and pathological features of periampullary region adenocarcinoma with an indeterminable origin. (19th May 2021) - Komine, Ryuji; Kojima, Motohiro; Ishi, Genichiro; Kudo, Masashi; Sugimoto, Motokazu; Kobayashi, Shin; Takahashi, Shinichiro; Konishi, Masaru; Kobayashi, Tatsushi; Akimoto, Tetsuo; Murakami, Ayumi; Sasaki, Motoko; et al.
Abstract: Determination of the primary tumor in periampullary region carcinomas can be difficult, and the pathological assessment and clinicopathological characteristics remain elusive. In this study, we investigated the current recognition and practices for periampullary region adenocarcinoma with an indeterminable origin among expert pathologists through a cognitive survey. Simultaneously, we analyzed a prospective collection of cases with an indeterminable primary tumor diagnosed from 2008 to 2018 to elucidate their clinicopathological features. All cases with pathological indeterminable primary tumors were reported and discussed in a clinicopathological conference to elucidate if it was possible to distinguish the primary tumor clinically and pathologically. From the cognitive survey, over 85% of the pathologists had experienced cases with indeterminable primary tumors; however, 70% of the cases was reported as pancreatic cancer without definitive grounds. Interpretation of the main tumor mass varied, and no standardized method was developed to determine the primary tumor. During a prospective study, 42 of the 392 periampullary carcinoma cases (10.7%) were considered as tumors with a pathological indeterminable origin. After the clinicopathological conferences, 21 (5.4%) remained indeterminable and were considered final indeterminable cases. Histological studies showed that the tumors spread along both the bile duct and main pancreatic duct; this was the most representative finding of the final indeterminable cases. This study is the first to elucidate and recognize the current clinicopathological features of periampullary region adenocarcinomas with an indeterminable origin. Adequate assessment of primary tumors in periampullary region carcinomas will help to optimize epidemiological data of pancreatic and bile duct cancer. Abstract : This study is the first to elucidate and recognize the current clinicopathological features of periampullary region adenocarcinomas with an indeterminable origin.